The Impact of Home Language and Literacy Environment on Children's Learning Outcomes - Budianto Hamuddin; Meutya Rizki Ramadhani; Fatma Setya Ningrum (Script Journal: Journal of Linguistics and English Teaching, 2025)
BackgroundThe Home Language and Literacy Environment (HLLE) is critical for children's language development, cognitive growth, and academic success. In bilingual and multilingual households, HLLE influences linguistic proficiency, executive function, and social integration. While numerous studies emphasize HLLE’s potential benefits, significant gaps remain concerning the influence of socioeconomic status, parental involvement, and access to technological tools in diverse home contexts. MethodologyThis Systematic Literature Review (SLR) synthesizes findings from 23 empirical studies (both qualitative and quantitative) published between 2019 and 2024, selected from 2,098 records across Crossref, Google Scholar, Scopus, and Web of Science. A thematic and quantitative synthesis categorizes results based on HLLE components, parental engagement, socioeconomic factors, and technology use.FindingsHLLE supports cognitive flexibility, literacy, and executive function. Parental involvement, especially in shared reading and storytelling, strongly links to higher vocabulary scores and literacy rates. Children in HLLE-rich environments show significant gains in language and reading, with vocabulary improvements of 20–30% and more conversational turns per hour, as measured by tools like LENA. Metrics such as adult word count and child vocalizations underscore HLLE’s impact. However, limited access to books, interactions, and technology due to socioeconomic gaps continues to widen literacy disparities. While tools like LENA offer valuable insights, challenges in accessibility and equity remain.ConclusionHLLE is essential for bilingual and multilingual literacy development. Addressing parental literacy support, socioeconomic inequalities, and digital literacy initiatives is crucial for equitable learning outcomes. Future research should assess HLLE’s long-term impact on academic success.OriginalityThis study offers a comprehensive synthesis of HLLE research, integrating linguistic, sociocultural, and quantitative perspectives to inform educators, policymakers, and researchers.